Adiwiyata-based school environment management: A multi-case study in Banjarmasin - Noviani Noviani; Ahmad Suriansyah; Sulistiyana Sulistiyana (Curricula: Journal of Curriculum Development, 2025)
The effectiveness of the Adiwiyata program is highly dependent on inspirational school leadership, ongoing training for teachers, and synergy between schools and supportive communities. This study aims to provide an in-depth description of how teacher empowerment, partnerships with various stakeholders, and school principal leadership strategies contribute to the environmental management of Adiwiyata-based schools. The research employed a multi-case study method with a descriptive qualitative approach. The study was conducted at two Adiwiyata schools in Banjarmasin: SDN-SN Pengambangan 5 Banjarmasin and SDIT Ukhuwah 2 Banjarmasin. Data collection techniques included in-depth interviews, direct field observations, and analysis of relevant documents. The findings indicate that the successful implementation of the Adiwiyata Program in both schools is strongly influenced by three key factors: first, teacher empowerment, reflected in active involvement in environmental teams and the integration of environmental awareness values into the learning process; second, effective partnerships between schools, local governments, foundations, and surrounding communities; and third, school leadership that is adaptive, collaborative, and capable of fostering a school culture oriented toward environmental conservation. These findings provide an example of best practices that can serve as a reference for other schools in developing sustainable and integrated environmental programs within their educational ecosystems.   Abstrak Efektivitas program Adiwiyata sangat tergantung pada kepemimpinan kepala sekolah yang inspiratif, pelatihan berkelanjutan bagi guru, dan sinergi antara sekolah dan komunitas yang mendukung. Penelitian ini bertujuan untuk mendeskripsikan secara mendalam bagaimana pemberdayaan guru, kemitraan dengan berbagai pihak, serta strategi kepemimpinan kepala sekolah berkontribusi dalam pengelolaan lingkungan sekolah berbasis Adiwiyata. Metode yang digunakan adalah studi multi kasus dengan pendekatan kualitatif deskriptif. Penelitian ini dilakukan di dua sekolah Adiwiyata Banjarmasin, yaitu di SDN-SN Pengambangan 5 Banjarmasin dan SDIT Ukhuwah 2 Banjarmasin. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi langsung di lapangan, serta analisis dokumentasi yang relevan. Hasil penelitian menunjukkan bahwa keberhasilan implementasi Program Adiwiyata di kedua sekolah tersebut sangat dipengaruhi oleh tiga faktor kunci: pertama, pemberdayaan guru yang tercermin dari keterlibatan aktif dalam tim lingkungan dan pengintegrasian nilai-nilai peduli lingkungan dalam pembelajaran; kedua, kemitraan yang efektif antara sekolah dengan pemerintah daerah, yayasan, serta masyarakat sekitar; dan ketiga, kepemimpinan kepala sekolah yang bersifat adaptif, kolaboratif, serta mampu membangun budaya sekolah yang berorientasi pada pelestarian lingkungan. Temuan ini memberikan gambaran praktik baik yang dapat dijadikan rujukan oleh sekolah lain dalam mengembangkan program lingkungan yang berkelanjutan dan terintegrasi dalam ekosistem pendidikan. Kata Kunci: Adiwiyata; manajemen lingkungan; sekolah Adiwiyata